Wave propagation as a marker of structural and topographic properties of human skin. (21st May 2018) - Djaghloul, M; Abdouni, A; Thieulin, C; Zahouani, H
Abstract: Chronological skin ageing is a phenomenon which imposes structural and functional changes on the cutaneous tissue. Mechanically, these changes can be related to structural rearrangements of the cutaneous tissue on surface and in volume (layers thickness). At the micro-structural level, the constitutional elements of the skin, collagen and elastin fibres, undergo also this rearrangement. The evolution of skin's mechanical properties at this level is the origin of a primordial in-vivo mechanical characteristic known as the natural pretension. In the context of understanding the in-vivo skin mechanical behaviour, related to the natural pretension, a lot of instrumentations have been demonstrated in the literature. They are mainly based on the interaction between dynamic adapted solicitation and the observed reaction on the skin. In this study, we evaluate the mechanical behaviour of human skin, following an impact which induces wave propagation. The use of impact solicitation allows the direct correlation between the dynamic induced reaction (vibration, and wave propagation) of the cutaneous tissue and its mechanical property. In our development, impact solicitation is contactless, with an air blast as generator of local deformation. The estimation of the speed of wave propagation enables the characterization of the mechanical behaviour of the skin. In order to validate the developed approaches, to understand the chronological ageing, gender and anisotropy effects on the skin properties, measurements have been realized on 77 healthy volunteers separated in five age groups. The obtained results are consistent with earlier works and confirm the efficiency of the developed instrumentation to estimate the changes of mechanical behaviour of the skin under age and gender effects.